The Role of TikTok in Shaping Wan Music Trends in Thailand: A Digital Ethnography during the COVID-19 Pandemic - Paprach, Thapthep; Lertsuwan, Benya; Saardprai, Phatruthai (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The advent of digital technology has changed music consumption patterns, driving trends. The emergence of platforms such as TikTok as major influencers in contemporary music composition trends. Due to the disturbing impact of the COVID-19 pandemic on traditional income streams within the music industry. Online platforms like TikTok have gained a new reputation in the music industry as a ways to promote and participate in music. This paper is an in-depth analysis examination of TikTok’s role as a form of User Generated Content (UGC) and its consequent impact on the Thai music industry, with a specific focus on the genre known as "Wan music." Qualitative research methods, including participatory observation and data analysis, the The study sheds light on the ways in which TikTok users, predominantly females, interact with and propagate Wan songs, thus enhancing the vibrant community around this musical genre. Through an extensive literature review including original fieldwork, seminal works in the fields of digital ethnography, social media research, and music marketing. This paper empirical findings in a broader theoretical framework. By integrating existing scholarship studies shed light on topics such as digital ethnography, UGC, and music marketing on the nuanced dynamics at play within the intersection of TikTok, Thai music, and the COVID-19 pandemic. The findings underscore the transformative influence of TikTok as a catalyst for music discovery, dissemination, and audience engagement, particularly within the unique socio-cultural milieu of Thailand during a period of global upheaval. Ultimately, this paper contributes to a deeper understanding of the multifaceted role played by digital platforms in reshaping contemporary music ecosystems, offering insights that are pertinent not only to scholars and practitioners in the fields of media studies and musicology but also to stakeholders within the broader creative industries landscape.